Animated Stories: It’s Effect on Students’ Scores in Reading Comprehension Score - Faida Azhimia (Journal Corner of Education, Linguistics, and Literature, 2023)
Teaching English through animated stories bears much potential for effective and meaningful language instruction as animated stories can help to contextualize the new language by providing auditory and visual presentation material. This study investigates the effect of animated stories on students’ reading comprehension skills of narrative texts across different personalities. This quasi-experimental design study involved 63 junior high school students, 32 for the experimental and 31 for the control classes, who were randomly selected. This study employed four authentic animated stories as the theme to teach the narrative text. The treatment was carried out in four meetings, and subsequent to the treatment, the reading comprehension test was conducted. The main data was collected from the post-test and questionnaire. The test is in the form of multiple choice with 20 items and four options. The data analysis result showed a significant effect of animated stories on the student’s reading comprehension skills of narrative texts. The experimental class's mean score was higher than the control class's mean score. Students in the animated stories group achieved higher scores than those in the control group, with a mean difference of 11.431. This finding confirms the theory that multimedia, particularly animated stories, effectively improves students’ reading comprehension.